Odpowiedzi

Najlepsza Odpowiedź!
2010-01-28T00:09:15+01:00
1)
a₇-a₃=8
a₂*a₇=75

a₂=a₁+r
a₃=a₁+2r
a₇=a₁+6r

a₁+6r-(a₁+2r)=8
(a₁+r)*(a₁+6r)=75

a₁+6r-a₁-2r=8
a₁²+6ra₁+ra₁+6r²=75

4r=8 /:4
a₁²+7ra₁+6r²=75

r=2
a₁²+7*2a₁+6*2²=75

a₁²+14a₁+24-75=0
a₁²+14a₁-51=0

Δ=14²-4*(-51)=196+204=400
√Δ=20
a₁=(-14-20)/2=-34/2=-17
lub
a₁=(-14+20)/2=6/2=3

r=2

2)
a₄:a₆=-1
a₂*a₈=-1

a₂=a₁+r
a₄=a₁+3r
a₆=a₁+5r
a₈=a₁+7r

(a₁+3r):(a₁+5r)=-1 /*(a₁+5r)
(a₁+r)*(a₁+7r)=-1

(a₁+3r)=-(a₁+5r)
a₁²+7ra₁+ra₁+7r²=-1

a₁+3r=-a₁-5r
a₁²+8ra₁+7r²=-1

a₁+a₁=-5r-3r
a₁²+8ra₁+7r²=-1

2a₁=-8r /:2
a₁²+8ra₁+7r²=-1

a₁=-4r
(-4r)²+8r(-4r)+7r²=-1

16r²-32r²+7r²=-1
-16r²+7r²=-1
-9r²=-1 /:(-9)
r²=1/9
r=1/3
a₁=-4r=-4/3

lub
r=-1/3
a₁=-4r=4/3
4 3 4